A study on lane changing behavior of Filipino drivers on an urban street - Cua, Jeremy Rainier O.
This study was conducted to characterize the behavior of Filipino drivers on urban streets. The two parameters considered in characterizing driver behavior were lane change duration and gap acceptance under different traffic flow rates. Data were collected during various times of regular weekdays to adequately cover different flow rates. Video surveillance was conducted at selected road sections bound by signalized intersections. This study focused on the analysis of lane changes performed by different vehicle types such as passenger cars, medium vehicles, and heavy vehicles. Statistical analysis was performed to generate descriptive statistics and best fit distributions of the collected data for both lane change duration and accepted gap size. The use of Two-Sample t-Test hypothesis testing showed that there is no statistical difference in the mean values of lane change duration under different traffic flow rates. The same hypothesis test determined that there is significant difference between the mean values of accepted gaps between the lowest and highest traffic flow rates. Drivers took the same time to change lanes regardless of the traffic condition, but accepted smaller gaps as the flow rate increased. Filipino drivers were observed to take more time changing lanes, while accepting smaller gaps than drivers from previous studies. The findings from this study could serve as localized parameters for traffic simulations models for the Philippine setting.